Non-local drivers of the summer hypoxia in the East China Sea off the Changjiang Estuary. (5th November 2017) - Qian, Wei; Dai, Minhan; Xu, Min; Kao, Shuh-ji; Du, Chuanjun; Liu, Jinwen; Wang, Hongjie; Guo, Liguo; Wang, Lifang
Abstract: The East China Sea (ECS) off the Changjiang (Yangtze River) Estuary, located around the near field of the Changjiang plume (CJP) is a hot spot where phytoplankton blooms in the surface water and hypoxias in the subsurface/bottom waters are frequently observed. Based on field observations conducted in summer 2009 and 2011, we examined non-local drivers associated with the initial dissolved oxygen (DO) levels that had significant impact on the development of summer hypoxias in the ECS off the Changjiang Estuary. The bottom water mass therein could be traced isopycnally at 24.2 < σ θ  < 25.2 back to the vicinity of the Luzon Strait, ∼1300 km upstream, where subsurface Kuroshio water (∼220 m deep with ∼190 μmol DO kg −1 ) mixed with the South China Sea subsurface water (∼120 m deep with ∼130 μmol DO kg −1 ). Owing to the difference in DO of these two source water masses, their mixing ratio ultimately determined the initial DO supply to the ECS bottom water that eventually reached the hypoxic zone. This water mass mixture was also subject to biogeochemical alteration during its travel (∼60 days) after it intruded into the ECS at the northeastern tip of Taiwan. Along the pathway of the intruded bottom-hugging water, we found systematic increases in nutrient concentrations and apparent oxygen utilization, or drawdown in DO following Redfield stoichiometry as a result of marine organic matter decomposition. These non-local factors exerted a synergistic control on the initial DO of CJP bottom water promoting hypoxia formation, although the residence time of the CJP bottom water was relatively short (∼11 days). We contend that such far field drivers should be taken into account in order to better predict the future scenarios of coastal hypoxias in the context of global warming. Highlights: The initial DO of the source water masses controls significantly the hypoxia in the East China Sea. The evolution of DO on the pathway to the hypoxic zone also matters. Stoichiometry is useful in tracing the water mass and biogeochemical alteration along the flow path.